2019
DOI: 10.33192/smj.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

An Association of Cryptococcus Neoformans/C. gattii Genotype and HIV Status in Asia: A Systematic Review

Abstract: Objective: It has been known that VNI molecular type of Cryptococcus neoformans/C. gattii is strongly associated with HIV patients. However, this paradigm has recently been challenged because of the high prevalence of VNI molecular type among non-HIV patients with cryptococcosis in East Asia. The purpose of this study was to answer the question: "Among cryptococcosis in Asia, is there an association between the genotype and the patient's HIV status?" Methods: Using a systematic review and meta-analysis study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Further genotype analysis of C. neoformans by MLST showed that ST5/VNI was the most common genotype (43/164 isolates; 26.2%) among the clinical isolates of C. neoformans. This result is similar to the findings of a recent systematic review of Asian cryptococcosis in which ST5/VNI was reported to be the most common genotype among non-HIV patients in both East Asian (87.9%) and other Asian (39.3%) countries [52]. Our findings is also similar to what has been reported for Vietnam (83.7%) [47] and Laos (25%) [53].…”
Section: St5 (N = 47)supporting
confidence: 92%
See 1 more Smart Citation
“…Further genotype analysis of C. neoformans by MLST showed that ST5/VNI was the most common genotype (43/164 isolates; 26.2%) among the clinical isolates of C. neoformans. This result is similar to the findings of a recent systematic review of Asian cryptococcosis in which ST5/VNI was reported to be the most common genotype among non-HIV patients in both East Asian (87.9%) and other Asian (39.3%) countries [52]. Our findings is also similar to what has been reported for Vietnam (83.7%) [47] and Laos (25%) [53].…”
Section: St5 (N = 47)supporting
confidence: 92%
“…Three other common genotypes-namely, ST2/VNI (13.2%), ST63/VNI (9.8%), and ST40/VNII (9.8%)-were reported in Asia, Africa, Europe, and the United States [4,10,11,23,54]. Interestingly, the most common genotype among the environmental isolates, ST4/VNI (25%), was also the most common (32.6%) sequence type isolated from HIV patients outside of the East Asian countries [52]. This result concurs with the proposal that HIV patients contracted cryptococcosis from their environment as the diversity of the genotypes in the environment is reflected in the clinical isolates [55].…”
Section: St5 (N = 47)mentioning
confidence: 98%